CT appearance of acute pancreatitis using multiphase Multidetector Computed Tomography and correlation between CT Severity Index and clinical outcomes - Jiruppabha, Busaba (Chulalongkorn Medical Journal, 2023)
Background: Pancreatitis is one of the most complicated and clinically challenging of all abdominal disorders. Computed tomography (CT) is highly accurate and sensitive in both diagnosing and demonstrating its extent. In Thailand, in spite of the importance of the disease, there are a few studies of acute pancreatitis (AP), which mainly focus on its management. Currently, the 2012 revision of the Atlanta classification including new terminology and clinical assessment of the severity of AP is used. Objective: To describe CT findings of AP using the 2012 revision of the Atlanta classification and association between CT severity index (CTSI) with clinical outcomes. Methods: The multiphase multidetector computed tomography (MDCT) imaging (nonenhanced, hepatic arterial and portovenous phases) and relevant clinical data of 53 AP patients were reviewed. The diagnosis of AP met two of the three diagnostic criteria (abdominal pain, a serum amylase level three times higher than the upper limit of normal and pancreatitis documented by CT). Results: The most common CT findings were extrapancreatic inflammatory changes (fat stranding and/or acute pancreatic necrosis; ANC) 87%, involving anterior pararenal space 85%, left anterior pararenal space 51%, pancreatic enlargement 77%, focal enlargement of the pancreas 43%, necrotizing pancreatitis 60%, combined necrosis 34%, bilateral pleural effusion 44%, local complication 55%, ANC 49%, gastrointestinal wall thickening 32%, involving duodenum 23%, and Balthazar CTSI significantly associated with intervention/drainage, surgical debridement and death (P < 0.05). No association was detected between Balthazar CTSI and organ failure. The revised Atlanta classification severity grading was associated with all clinical outcomes. Death was only seen in severe grading scores according to the revised classification. Conclusion: The most common CT findings of AP at Bangkok Metropolitan Administration General Hospital were extrapancreatic inflammatory changes including fat stranding and/or ANC at the anterior pararenal space, prominent on the left side, pancreatic enlargement especially focal pancreatic enlargement, pancreatic necrosis mainly combined necrosis, bilateral pleural effusion and duodenal wall thickening. The higher incidence of pancreatic necrosis in this study was due to the new definition according to the 2012 revision of the Atlanta classification. There was no association between Balthazar CTSI and organ failure. The revised Atlanta classification severity grading was associated with all clinical outcomes, especially death.